Tazkiyah sebagai Epistemologi Irfani: Perspektif Wahiduddin Khan tentang Spiritualitas Perdamaian - Muhammad Taufik Ismail; Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Religious views which tends to be exoteric and only looking at the formal legal aspect, often gives an over-sensitive views, emotional, and unconsciously giving violence actions. Wahiduddin Khan is a figure who aware of this problem, so he develope the concept of tazkiyah as the basis for the spirituality of peace. Tazkiyah according to Khan focused on intellectual development that touches the heart, so it built the integration between rationality and spirituality which is construct the forms a complete human being. This research was conducted with a descriptive qualitative approach through literature review. This research founded four stages of four stages of tazkiyah: abstraction, internalization, transcendence, and humanization. Tazkiyah is a combination of rational awareness, feelings in the heart (spiritual events) and practical actions that connecting two currents of centripetal and centrifugal motion. The inward movement is closer to mystical awareness and the outward movement is a form of participation in building traditions and social institutions. This combination will produce spirituality that manifests in the awareness and attitude of peace.